Nanopatterning of a Stimuli-Responsive Fluorescent Supramolecular Polymer by Thermal Scanning Probe Lithography - Zimmermann, Samuel Tobias (ACS Appl Mater Interfaces, 2017)
[Image: see text] The miniaturization of nanometer-sized multicolor fluorescent features is of continuous significance for counterfeit security features, data storage, and sensors. Recent advances in engineering of stimuli-responsive supramolecular polymeric materials that respond upon exposure to heat or mechanical force by changing their fluorescence characteristics open new opportunities as functional lithographic resists. Here, we demonstrate the patterning of a thermochromic supramolecular material by thermal scanning probe lithography (t-SPL), an emerging nanofabrication technique, which allows for ultrafast indentation with a heated probe, resulting in both fluorescent and topographic nanofeatures. t-SPL indentation reveals a linear relationship between the temperature at which material softening occurs and the indentation force in the range from 200 to 500 nN. The softening temperature decreases as the heating time increases from 4 μs to 1 ms, following time–temperature superposition behavior. Our results herein confirm that the fluorescence contrast, perceivable as a shift from red to green, was obtained by kinetic trapping of the dissociated state due to ultrarapid cooling when the probe is removed. We use t-SPL to create highly customized fluorescence patterns up to 40 × 40 μm(2) in size with a spatial resolution of 86 nm and change the pitch size to modify the fluorescence intensity when observed by fluorescence microscopy. As an application, multifaceted security features with nanometer resolution are explored.